Spectroscopic Elucidation and Anticancer Potential of 7-methoxy-2-(4-methoxyphenyl)-5-O-glycosyl chromenone Isolated from Haplanthodes tentaculatus (L.) R. B. Majumdar (International Journal of Pharmaceutical Sciences and Drug Research, 2024)
In this research, we report on the isolation and structural elucidation of a new flavonoid glycoside called 7-methoxy-2-(4-methoxyphenyl)-5-O-glycosyl chromenone. This flavonoid glycoside was obtained from Haplanthodes tentaculatus, a plant that is native to the Western Ghats of India. The molecule was purified via the use of chromatographic procedures, and its structure was validated by the use of spectroscopic investigations, which included HRMS, 1H NMR, 13C NMR, FTIR, and UV-Visive technologies. With the use of HRMS analysis, the chemical formula C₂₃H₂₄O₁₀ was verified. The isolated molecule demonstrated anticancer activity in vitro against the MDA-MB-231 breast cancer cell line, with an IC₅₀ value of 58.99 ± 0.495 µg/ml. This indicates that the drug is very effective in curing cancer. The natural origin of 7-methoxy-2-(4-methoxyphenyl)-5-O-glycosyl chromenone and the possibility that it has a reduced toxicity level imply that it has the potential to be a lead molecule for the creation of anticancer drugs, despite the fact that it is less effective than the conventional medicine Cisplatin. The findings of this research add to the increasing body of evidence that bioactive chemicals derived from natural sources have the potential to be used in therapeutic medicine.